Prevention of bronchiolitis from the hospital to home: enviromental and pharmacological strategies - Andrea Dotta (Hygeia Press di Corridori Marinella, 2015)
Bronchiolitis is one of the major cause of mortality and morbidity during infancy, with high hospitalization rate during epidemic season for high risk infants during the first year of life. There is no specific therapy with proven efficacy apart hydration and hypertonic saline. Mild forms can be treated in outpatient setting avoiding a useless hospitalization. Enviromental prevention is crucial in hospital setting, in outpatient ambulatory and at home: for this purpose hand hygiene, tobacco exposure, breastfeeding must be emphasized with families and caregivers. Pharmacological prophylaxis uses a humanized monoclonal antibody (palivizumab) shown effective in reducing hospitalization rate in preterm infants < 35 weeks gestational age, infants with bronchopulmonary dysplasia and infants with congenital heart disease. During the last 2 years different recommandations and guidelines confirmed the importance of prophylaxis with palivizumab with some differences between Groups and Societies based on different healthcare systems. In any case it is important a good contact between hospital and all caregivers of these patients to reduce the viral exposure and increase the defense capability of high risk patients.   Proceedings of the 11th International Workshop on Neonatology and Satellite Meetings · Cagliari (Italy) · October 26th-31st, 2015 · From the womb to the adult Guest Editors: Vassilios Fanos (Cagliari, Italy), Michele Mussap (Genoa, Italy), Antonio Del Vecchio (Bari, Italy), Bo Sun (Shanghai, China), Dorret I. Boomsma (Amsterdam, the Netherlands), Gavino Faa (Cagliari, Italy), Antonio Giordano (Philadelphia, USA)